Temperature and bias voltage dependences of magnetic tunnel junction with FeAlSi electrode - Shoma Akamatsu; Byung Hun Lee; Yasen Hou; Masakiyo Tsunoda; Mikihiko Oogane; Geoffrey S. D. Beach; Jagadeesh S. Moodera (APL Materials, 2024)
We fabricated magnetic tunnel junctions (MTJs) with FeAlSi free layers and investigated the tunnel magnetoresistance (TMR) properties. We found that the temperature and bias voltage dependences of the TMR effect in FeAlSi-MTJs were almost the same as MTJs with Fe free layers despite the low Curie temperature of FeAlSi. In the inelastic electron tunneling spectroscopy measured at low temperatures, the relatively large cutoff energy of magnon excitation at the FeAlSi and MgO interface was confirmed. In addition, we studied for the first time the exchange stiffness constant of FeAlSi films by Brillouin light scattering. The determined value of the stiffness constant of FeAlSi was 14.3 (pJ/m), which was similar to that of Fe. Both the large magnon cutoff at the interface and the stiffness constant of FeAlSi are considered to be the reason for the good temperature and voltage dependences of FeAlSi-MTJs.